2008
DOI: 10.4103/0255-0857.42035
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-β-lactamase-producing clinical isolates of <i> Acinetobacter</i> species and <i> Pseudomonas aeruginosa</i> from intensive care unit patients of a tertiary care hospital

Abstract: Prompt detection of metallo-β-lactamase (MBL) producing isolates is necessary to prevent their dissemination. Frequency of MBLs producing strains among multidrug resistant (MDR) Acinetobacter species and Pseudomonas aeruginosa was evaluated in critical care patients using imipenem-EDTA disk method. One hundred MDR Acinetobacter spp. and 42 Pseudomonas aeruginosa were checked for MBL production, from January to June 2001. MBL was produced by 96.6 % of imipenem-resistant Acinetobacter isolates, whereas 100% imip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 8 publications
8
33
2
1
Order By: Relevance
“…Shali Preet Sidhu et al [10] reported that 6.97% of the Pseudomonas aeruginosa showed resistance to the carbapenems, and it is coinciding with the present study. Irfan et al [4] reported (100%) of the carbapenem resistant isolates of Pseudomonas aeruginosa were MBL producers, which are also coinciding with the study. All the pathogenic cultures which were isolated in the current investigation showed 100% sensitivity to Polymyxin-B.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Shali Preet Sidhu et al [10] reported that 6.97% of the Pseudomonas aeruginosa showed resistance to the carbapenems, and it is coinciding with the present study. Irfan et al [4] reported (100%) of the carbapenem resistant isolates of Pseudomonas aeruginosa were MBL producers, which are also coinciding with the study. All the pathogenic cultures which were isolated in the current investigation showed 100% sensitivity to Polymyxin-B.…”
Section: Discussionsupporting
confidence: 85%
“…So this enzyme is responsible for multidrug resistance, and they possess high hydrolytic activity that leads to degradation of higher generation cephalosporins. Plasmid mediated MBL genes spread rapidly to other species of gram negative bacilli, therefore rapid detection of metallo-beta-lactamase production is necessary to modify therapy and to initiate effective infection control to prevent their dissemination [4]. So identification of metallo-beta-lactamase producing non-fermenters was also included in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Polymyxin discs of 300 units were used for susceptibility testing [1,12,13]. The disc diffusion technique was reported to be an unreliable method for evaluating the susceptibility of bacteria to polymyxins because these antibiotics diffuse poorly in agar.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…Out of that rate of MBL producing strain by disc potentiation test was 77.8% and that of by E strip technique was 74.07%. Irfan et al, have reported 97% of the MBL producing Acinetobacter species by Disc potentiation technique (Irfan et al, 2008). In one of the Indian study on the Acinetobacter baumanii species stated that 70.9% of these isolates produced metallo beta lactamase by Disc potentiation technique, while another study reported from Kerala, India, states that 21% of the Acinetobacter baumannii isolates were found to be metallo-β-lacatmase producers (Uma et al, 2009;Anil et al, 2011).…”
Section: Resultsmentioning
confidence: 99%